Diseño lumínico eficiente para el bloque A3 de la UNL - Auquilla Tenezaca, Pablo David (2024)
Lighting is part of our daily life; we obtain it naturally through the sun's rays and artificially with the conversion of electrical energy into light. In 2016, it was estimated that the energy consumption used for lighting was 2900 TWh worldwide. It is projected that, in twenty years, energy consumption for lighting will increase by 50%. The objective of this work was to carry out a lighting study in the classrooms of block A3. To do so, a survey of the physical and technical information of the classrooms of block A3 of the UNL was carried out, with the purpose of measuring, simulating and obtaining technical data of the existing facilities for their respective analysis. Then, the new lighting system was calculated, designed and simulated, so that the measurement parameters comply with the requirements of the regulations. Finally, a control system was added to the projected lighting design, which allows the switching on and off of luminaires autonomously. It was found that 100% of the classrooms inspected do not meet the required levels of illumination and uniformity. When carrying out the projected design, the values of the parameters required for the lighting to be comfortable were met. The change of lighting and implementation of a control system has resulted in a projected saving of 55.22% in annual electricity bills. The evaluation of the interior lighting system revealed that 100% of the classrooms evaluated do not comply with the lighting parameters suggested by the UNE-12464-1-2022 standard. The projected design reduced the installed power by 29.68%, which contributes to energy efficiency. In addition, the control system prevents the luminaires from remaining on, preventing energy losses. Keywords: Energy efficiency, lighting, regulations, comfort, optimize.